2017
DOI: 10.1044/2016_jslhr-l-15-0358
|View full text |Cite
|
Sign up to set email alerts
|

Noncomprehension Signaling in Males and Females With Fragile X Syndrome

Abstract: a,bPurpose: This study used a prospective longitudinal design to evaluate the trajectory and predictors of noncomprehension signaling in male and female youth with fragile X syndrome (FXS). Method: A direction-following task in which some of the directions were inadequate was administered. Participants were 52 youth (36 boys, 16 girls) with FXS. Upon study entry, participants ranged from 10 to 16 years. The average number of annual assessments per participant was 3.65 (range = 1-4), providing 198 data points f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 83 publications
0
8
1
Order By: Relevance
“…These findings are not necessarily surprising, given that females with FXS (with and without ASD) are typically less severely affected than males, due to the presence of a second X chromosome (thus one normally functioning copy of FMR1; Hagerman et al, 1992). Of note, previous studies of sex differences in communication repair skills in FXS have yielded mixed results; whereas two studies indicated better signaling of noncomprehension of a confusing message in females with FXS compared with males (Abbeduto et al, 2008;Thurman et al, 2017), research from our group did not detect sex differences in individuals with FXS-O or FXS-ASD (Martin et al, 2017). Additionally, TD females tend to develop social communicative skills earlier than males (Blakemore, Berenbaum, & Liben, 2008).…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…These findings are not necessarily surprising, given that females with FXS (with and without ASD) are typically less severely affected than males, due to the presence of a second X chromosome (thus one normally functioning copy of FMR1; Hagerman et al, 1992). Of note, previous studies of sex differences in communication repair skills in FXS have yielded mixed results; whereas two studies indicated better signaling of noncomprehension of a confusing message in females with FXS compared with males (Abbeduto et al, 2008;Thurman et al, 2017), research from our group did not detect sex differences in individuals with FXS-O or FXS-ASD (Martin et al, 2017). Additionally, TD females tend to develop social communicative skills earlier than males (Blakemore, Berenbaum, & Liben, 2008).…”
Section: Discussioncontrasting
confidence: 82%
“…The limited studies on communication breakdown in FXS and DS have focused primarily on the ability to signal noncomprehension (confusion) when presented with unclear messages. For example, studies found that individuals with DS (Abbeduto et al, 2008;Martin et al, 2017) and FXS (Abbeduto et al, 2008;Thurman, Kover, Brown, Harvey, & Abbeduto, 2017) were less likely than TD controls to signal noncomprehension of a confusing message, with additional evidence that comorbid ASD negatively impacts this skill in FXS (Martin et al, 2017). No studies other than the study by Levy et al (2003), which included one male with FXS, have examined the ability of individuals with FXS to repair their own statements, and only one case study of four children has investigated repair skills in DS, with findings showing appropriate responses to requests for clarification (Coggins & Stoel-Gammon, 1982).…”
Section: Pragmatics and Communication Repair In Different Neurodevelomentioning
confidence: 99%
See 1 more Smart Citation
“…Eligibility criteria also required hearing to be directly assessed into establish that pure tone thresholds no worse than 30 dB in the better ear. Several publications have emerged from the project (e.g., [8,26,59,103,104]), and some have included the conversational and narrative language measures and participants included in the present study; however, no other reports have focused on the longitudinal data from the measures of language included in the present study or the full range of predictors of language examined here.…”
Section: Methodsmentioning
confidence: 99%
“…These results can then be used as a point of comparison when examining the repair requests produced by children with weaknesses in social communication, such as children with autism spectrum disorder. Previous investigations have described limitations in repair requests produced by children with developmental disabilities that include children with intellectual disability, Down syndrome, Williams syndrome, and fragile X syndrome (e.g., Abbeduto, Davies, Solesby, & Furman, 1991;Abbeduto et al, 2008;Abbeduto, Short-Meyerson, Benson, & Dolish, 1997;John, Rowe, & Mervis, 2009;Skwerer, Ammerman, & Tager-Flusberg, 2013;Thurman, Kover, Brown, Harvey, & Abbeduto, 2017). However, results from these studies have been mixed potentially due to differences in study methods.…”
mentioning
confidence: 99%